Pengaruh Brand Awareness, Brand Image dan Customer Perceived Value Terhadap Purchase Intention - Luki Lukmanul Hakim; Keni Keni (Universitas Tarumanagara, 2020)
This study aims to determine the effect of brand awareness, brand image, and customer perceived value on purchase intentions. The sampling technique used in this study is nonprobability sampling by purposive sampling using a quantitative approach by distributing questionnaires to 146 which valid respondents 142 respondents. Data analysis method used in this study is multiple regression analysis. For operational variables using the Likert scale method of validity used a computer measuring instrument that is SPSS 25.0. The results showed that the brand awareness variable have a significant and positif effect, brand image have a significant and positif effect, customer perceived value have a significant and positif effect on purchase intention. In this case the brand image is the most influences of purchase intention.